Analysis of health expenditures in China from 2000 to 2019 compared with the world and upper-middle-income countries - Zeng, Xindian; Chen, Lijie; Chen, Lu (Frontiers in Public Health, 2025)
BackgroundFairness in health funding has always been a priority in China. This article aims to study the trends in total health expenditure (THE), government health expenditure (GHE), social health expenditure (SHE), and out-of-pocket health expenditure (OOPHE) among China, the world, and upper-middle-income countries from 2000 to 2019. The goal is to provide a theoretical basis for the Chinese government to adjust and formulate health-related policies.MethodsAggregate time-series data were collected from the World Health Organization (WHO) and the World Bank (WB) Open Data sources from 2000 to 2019. These data were compared and some of it analyzed using cluster analysis methods.ResultsThe financing structure level of THE in China is currently above average among upper-middle-income countries. The proportion of THE in GDP for upper-middle-income countries and China remains relatively stable and slow growth, and is consistently lower than the world average. The proportions of GHE and SHE in THE in China and upper-middle-income countries converged toward the world average level. But the proportion of OOPHE in THE in China is higher than that of two. Overall, the proportions of GHE exhibited an upward trend and the proportion of SHE and OOPHE exhibited a downward trend in China. What's more, the changes in China are more pronounced. The proportion of THE in GDP of China increased by 0.84% from 2000 to 2019, and it ranked 24th among the 51 upper-middle-income countries in 2019, and Compared with it in 2000 there has been a consistently positive increase rate. The per capita health expenditure in China was $42.11 in 2000 and it's $535.13 in 2019, which rapidly grow to the level of upper-middle-income countries and narrow the gap with the level of the world.ConclusionThe financing structure of THE is increasingly optimized, but the level of financing still needs improvement in China. The government should continue to optimize the financing structure of THE, increase GHE, encourage social capital investment, decrease the proportion of OOPHE, diversify financing and reimbursement policies to promote hierarchical medical system, promote health management for an aging population, and formulate health expenditure plans for public health emergencies.